Differential relationships of family drinking with alcohol expectancy among urban school children - Chen Kuang-Hung; Liu Chieh-Yu; Storr Carla L; Chen Chuan-Yu; Chen Wei J; Lin Keh-Ming (BMC, 2011)
Abstract Background Positive alcohol outcome expectancy has consistently been linked with problematic drinking, but there is little population-based evidence on its role on early stages of drinking in childhood. The present study seeks to understand the extent to which drinking of family members is differentially associated with the endorsement of alcohol expectancy in late childhood. Methods A representative sample of 4th and 6th graders (N = 2455) drawn from 28 public schools in an urban region of Taiwan completed a self-administered paper-and-pencil questionnaire. Each student provided information on alcohol expectancy, drinking experiences, and individual and family attributes. Complex survey analyses were performed to evaluate the relationship, with stratification by children's alcohol drinking history. Results An estimated 29% of the 4th graders and 43% of the 6th graders had initiated alcohol consumption (over 40% of them had drank on three or more occasions). Alcohol drinking-related differences appear in both the endorsement and the correlates of alcohol expectancy. Positive alcohol expectancy was strongly associated with family drinking, particularly the dimension of "enhanced social behaviors"; negative alcohol expectancy was inversely associated with drinking frequency. Among alcohol naïve children, significant connections appear between paternal drinking and three dimensions of positive alcohol expectancy (i.e., enhanced social behaviors:βwt = 0.15, promoting relaxation or tension reduction:βwt = 0.18, and global positive transformation:βwt = 0.22). Conclusions Individual tailored strategies that address family influences on alcohol expectancy may be needed in prevention programs targeting drinking behaviors in children.